2014
DOI: 10.1371/journal.pone.0097793
|View full text |Cite
|
Sign up to set email alerts
|

Alternatively Spliced Tissue Factor Is Not Sufficient for Embryonic Development

Abstract: Tissue factor (TF) triggers blood coagulation and is translated from two mRNA splice isoforms, encoding membrane-anchored full-length TF (flTF) and soluble alternatively-spliced TF (asTF). The complete knockout of TF in mice causes embryonic lethality associated with failure of the yolk sac vasculature. Although asTF plays roles in postnatal angiogenesis, it is unknown whether it activates coagulation sufficiently or makes previously unrecognized contributions to sustaining integrity of embryonic yolk sac vess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Although alternatively spliced TF (asTF) does not support physiological roles of TF (e.g. in embryonic development ), it retains the ability to ligate integrins αvβ3 and α6β1 , which also interact with full‐length TF . Signaling of asTF is independent of FVIIa‐PAR2 and promotes, through direct integrin ligation of endothelial cells, angiogenesis and inflammation , or cancer cell survival .…”
Section: Tf‐fviia and Intracellular Signalingmentioning
confidence: 99%
“…Although alternatively spliced TF (asTF) does not support physiological roles of TF (e.g. in embryonic development ), it retains the ability to ligate integrins αvβ3 and α6β1 , which also interact with full‐length TF . Signaling of asTF is independent of FVIIa‐PAR2 and promotes, through direct integrin ligation of endothelial cells, angiogenesis and inflammation , or cancer cell survival .…”
Section: Tf‐fviia and Intracellular Signalingmentioning
confidence: 99%
“…The alternative splicing of TF preserves binding with αvβ3 and α6β1 and soluble asTF can enhance tumorigenicity of luminal breast cancer cells through autocrine integrin β1 signaling as well as through endothelial cell αvβ3 ligation promoting sprouting angiogenesis and upregulation of myeloid cell adhesion molecules (68-70). While integrin ligation pathways of asTF and transmembrane TF are overlapping, asTF, unlike full-length TF, cannot rescue early embryonic failure of the yolk sac vasculature caused by TF-deficiency in mice (71). …”
Section: Tf Signaling In Tumorcells and Angiogenesismentioning
confidence: 99%
“…34 Congruently, as-TF promotes cancer proliferation through integrin β1 signaling, further highlighting the pivotal interconnection of CFs with integrins. 35 However, as-TF alone is not enough to promote the correct formation of the vasculature during embryogenesis, 36 suggesting that both isoforms are necessary to regulate blood vessel formation and maintenance. Indeed, already in 1996 it was demonstrated that fl-TF −/− mice dye during embryonic development due to vascular failure.…”
Section: Tissue Factormentioning
confidence: 99%
“…However, as-TF alone is not enough to promote the correct formation of the vasculature during embryogenesis, 36 suggesting that both isoforms are necessary to regulate blood vessel formation and maintenance. Indeed, already in 1996, it was demonstrated that fl-TF -/ - mice die during embryonic development due to vascular failure.…”
Section: The Role Of Several Coagulation Factors On Endothelial Cell ...mentioning
confidence: 99%